2004
DOI: 10.1097/01.ogx.0000109264.36598.41
|View full text |Cite
|
Sign up to set email alerts
|

The Births of Five Spanish Babies From Cryopreserved Donated Oocytes

Abstract: This randomized, prospective study was performed to compare 2 techniques used to reduce the size of an enlarged uterus before vaginal hysterectomy or laparoscopically assisted vaginal hysterectomy (LAVH). Thirty patients scheduled to undergo vaginal hysterectomy or LAVH were randomized to have uterine reduction performed using either bisection/morcellation (group I, n ϭ 14) or myometrial coring (group II, n ϭ 16). The 2 groups were comparable in clinical and demographic characteristics, including preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Yang et al required 17 frozen oocytes to achieve one pregnancy (seven pregnancies from 120 frozen and thawed oocytes) (19). In 2003, Fosas et al reported on the need for 22 frozen donor oocytes to achieve one pregnancy (four pregnancies using 88 frozen and thawed oocytes) (20). In our study, 3 out of 4 patients became pregnant, with a total of six embryos implanting and resulting in ongoing pregnancies, representing the need of only 13 frozen and thawed oocytes to achieve an implantation (six fetal heartbeats from 79 frozen and thawed oocytes).…”
Section: Discussionmentioning
confidence: 70%
“…Yang et al required 17 frozen oocytes to achieve one pregnancy (seven pregnancies from 120 frozen and thawed oocytes) (19). In 2003, Fosas et al reported on the need for 22 frozen donor oocytes to achieve one pregnancy (four pregnancies using 88 frozen and thawed oocytes) (20). In our study, 3 out of 4 patients became pregnant, with a total of six embryos implanting and resulting in ongoing pregnancies, representing the need of only 13 frozen and thawed oocytes to achieve an implantation (six fetal heartbeats from 79 frozen and thawed oocytes).…”
Section: Discussionmentioning
confidence: 70%
“…Higher survival rates were obtained when oocytes were cryopreserved in 0.3 mol/L vs. 0.2 mol/L sucrose (60% vs. 82%) and when longer exposure to the cryoprotectant (10.5 to 15 min) was used. Other investigators using comparable slow-freeze methods reported similar survival and fertilization rates but higher pregnancy rates, ranging from 33% per embryo transfer with autologous oocytes (36), up to 57.1% when cryopreserved donor oocytes were used (37,38).…”
Section: Recent Developments With Slow-freeze Methodsmentioning
confidence: 82%
“…Porcu et al (2)(3)(4) described the freezing of metaphase II (MII) oocytes by the slow-freezing method. Other groups using the slow-freezing protocol reported 43% to 90% survival rates (6,8,9,12,27) with PRs of 19% to 33%.…”
Section: Discussionmentioning
confidence: 94%
“…Since the first successful pregnancy from frozen human oocytes was reported 20 years ago (1), many researchers around the world have exerted great effort attempting to make this part of the infertility treatment armamentarium. For the most part, efforts have been focused on the conventional slow-freezing method (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). More recently, vitrification methods have been adopted and studied by many researchers (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%